Defining and measuring economic resilience to disasters - Rose, Adam (Disaster prevention and management, 2004)
Three difficulties confront researchers in the resilience arena. At the conceptual level, there is the need to identify resilient actions, including those that may seem to violate established norms, such as rational behavior. At the operational level, it may be difficult to model individual, group, and community behavior in a single framework. At the empirical level, it is especially difficult to gather data on resilience to specify models. The purpose of this paper is to summarize progress on all three planes. First, defines several important dimensions of economic resilience to disasters. Second, shows how computable general equilibrium modeling represents a useful framework for analyzing the behavior of individuals, businesses, and markets. Third, summarizes recent progress in the conceptual and empirical modeling of resilience, including the incorporation of disequilibria and the recalibration of key behavioral parameters on the basis of empirical data. Fourth, uses the results of a case study to illustrate some important issues relating to the subject.